Factorial (25) design for the extraction of V(IV) in the V(IV)-[SO42-](H+, Na+) ? Cyanex 302-kerosene system - Biswas, RK; Karmakar, AK (Bangladesh Journal of Scientific and Industrial Research, 2016)
The title system has been investigated from the modeling points of view. Equilibration time is 20 min and the significant extraction occurs above pH 2. Considering the constancy of the organic to aqueous phase ratio (1:1), the factors affecting the extent of extraction (value of log D or log CD) are [V(IV)], pH(eq), [Cyanex 302], [SO42-] and temperature (T). The levels of these factors chosen in experimentation are high (+) and low (-). Regression or model equation for the extraction of vanadium (IV) by Cyanex 302 is determined from 25 full factorial design. On abbreviating log[V(IV)], -log(1+4641.14x10-pH + (1.5x106)x10-2pH), log[Cyanex 302], -log(1+2.24 [SO42-]) and absolute temperatures as M, P, E, S and T, respectively, the model obtained is: log CD = 10.452-0.16M+1.0047P+2.0011E+1.0003S-2425.3729/T. From the regression model it is seen that there is no interaction effect between the factors under investigation. The model can describe the system well. Bangladesh J. Sci. Ind. Res. 51(1), 47-54, 2016